Convenience and the hierarchy of meal preparation. Cooking and domestic education in the Netherlands, 1910–1930. (1st November 2015) - Verriet, Jon
Highlights: Dutch domestic educators employed a hierarchy of values for making food choices. A variety of convenient options in cooking were welcomed by domestic educators. Economy and nutrition were considered more important than convenience in food choice. Abstract: The concept of convenience in food products and meal preparation has changed rapidly during the twentieth century. However, there is little investigation into the way attitudes towards this concept have changed, which curbs our understanding of the importance of, and need for, convenience today. This paper uses the magazine of the Dutch schools of domestic education to examine their stance on convenience in meal preparation during the 1910s and 1920s. Recipes and articles are quantitatively and qualitatively analysed to estimate the importance of convenience in food preparation and consumption. The results of this analysis show that there was a hierarchy of values with regard to food choice: convenience was definitely valued, but matters of frugality and nutrition generally dominated. This provides not just a nuanced image of the role of domestic education (demanding yet flexible), but it also gives insight into the mechanics of food choice, which may at least partly still apply today.